Authorship of the Original Doctor Who Library and Lotka's Law. Issue 1 (2nd January 2017) - Shenton, Andrew K.
ABSTRACT: The Doctor Who Library forms one of the longest running and most extensive fiction book series for children and young people, and its role in promoting literacy within these groups in the 1970s and 1980s was very considerable. This article investigates the authorship of the Library's 159 volumes, which, almost without exception, are novelizations of the serials making up the original version of Doctor Who that ran on British television between 1963 and 1989. The article explores how far authorship patterns are consistent with Lotka's Law and the kinds of tendencies that are highlighted by Bradford's Law. Although the relationship between the number of Doctor Who books and the number of the authors responsible for them does not accurately reflect the statistical proportions stated by Lotka's Law, the general patterns inherent in the Law do indeed prevail.